Contribution to the Promotion of Innovative and Climate-Smart Agroecology: Application to Agriculture and Livestock in the Haute Matsiatra Region, Madagascar - Rakotonirina M.D.L.; Razafindrazanakolona A.D.; Ramanampisoa V.E.; Rabesiaka R; Damy T.S.; Koto-te-Nyiwa Ngbolua; Robijaona Rahelivololoniaina B.; Muhammad Ridwan (Britain International for Academic Research (BIAR-Publisher), 2023)
Climate change (CC) is having negative impacts on agricultural production at global, national, and local scales. Climate risks to agriculture, livestock, and fisheries are expected to increase in the coming decades, particularly in low-income countries with low adaptive capacity such as those in Africa and Madagascar. In most African countries, agriculture must undergo a profound transformation to address the many challenges of CC, food insecurity, malnutrition, poverty, and environmental degradation. This